2018
DOI: 10.1080/01612840.2018.1522399
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mental Illness and the Challenges This Brings for District Nurses in Primary Care Settings

Abstract: Patients with mental illness generally make their initial healthcare contact via a registered nurse. Although studies show that encountering and providing care to care-seekers with mental illness might be a challenge, little research exists regarding Primary Care Nurses' (PCN) view of the challenges they face. The aim of this study was to qualitatively explore PCNs' reflections on encountering care-seekers with mental illness in primary healthcare settings. The results consist of three themes: constantly exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Kvarme et al (2016) reported that immigrant mothers of children with disabilities report greater health problems, such as headache and depressive symptoms, compared with fathers. Nurses, as the patient's first-contact healthcare provider, have the closest contact with patients (Bjorkman, Andersson, Bergström, & Salzmann-Erikson, 2018). Thus, nurses can serve a critical role in detecting health problems and performing nursing interventions that can improve the health and quality of life in immigrant mothers of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Kvarme et al (2016) reported that immigrant mothers of children with disabilities report greater health problems, such as headache and depressive symptoms, compared with fathers. Nurses, as the patient's first-contact healthcare provider, have the closest contact with patients (Bjorkman, Andersson, Bergström, & Salzmann-Erikson, 2018). Thus, nurses can serve a critical role in detecting health problems and performing nursing interventions that can improve the health and quality of life in immigrant mothers of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Staff experienced that these patients benefitted from communicating in writing rather than having a telephone conversation with a triage nurse. Other studies report similar findings from mental health nurses in primary care experiencing that embarrassment and shame can present a barrier for mental health patients to seek care, given that their concerns are often difficult to express in a conversation [ 27 ]. These findings, together with the flexibility offered through the platform to make contact when the problems were more acute or intense, suggest that services became more sensitive to the specific needs of these patients.…”
Section: Discussionmentioning
confidence: 72%
“…Nurses in various settings including clinics, schools, and communities are often individuals' first healthcare providers, holding the prime position to screen for adolescent depression (Bjorkman et al, 2018). The BDI is one of the most favored instruments in nursing practice and is recommended as a quick but reliable tool in many psychiatric nursing textbooks (Hagen, 2007).…”
Section: Discussionmentioning
confidence: 99%